ENHANCING FOREIGN LANGUAGE TEACHING THROUGH DIGITAL TOOLS AND RESOURCES - Bondarenko , Alexander; Gudkova , Nataliia (Collection of scientific papers «ΛΌГOΣ», 2023)
This article explores the pros and cons of using digital technologies in foreign language education. It highlights personalized learning, diverse materials, and increased engagement as advantages. However, it acknowledges the limitations of reduced social interaction and potential health effects. The article discusses speech simulators, apps, and digital resources like textbooks and dictionaries. It emphasizes the role of audiovisual tech and internet resources in developing speech and listening skills. The shift towards student-centered approaches and the integration of active methods is noted.